Immunological Features of Chronic Gastroduodenitis in Children on the Background of Giardiasis - K.T. Glushko; M.I. Kinash; A.B. Kabakova; I.Y. Shostak (Zaslavsky O.Yu., 2016)
In the article, we have analyzed the immunological features of chronic gastroduodenal pathology in children with concomitant giardiasis. Objective: tо identify specific immunological criteria for chronic gastroduodenal pathology on the background of giardiasis in children. Materials and methods. The study involved 54 children with damage to the gastric and duodenal mucosa. Depending on giardia invasion, all children were divided into two groups: І - 28 persons with diagnosed giardiasis, ІІ - 26 patients without invasion. 24 apparently healthy children were included in the control group. In all children, we have evaluated the concentrations of interleukin-4 (IL-4) and tumor necrosis factor α (TNF-α) in the blood serum, performed stool parasitological research. Results. H.pylori infection has been confirmed in 18 (33.3 %) children. The incidence of H.pylori infection in patients of both groups did not differ: in group I - 9 (32.1 ± 8.9 %), in group II - 9 (34.6 ± 9.5 %) cases (p > 0.05). It was found that the content of IL-4 in the examined children (8.0 ± 0.5 pg/ml) was higher compared with controls, whereas TNF-α level (2.7 ± 0.7 pg/ml) - did not differ. In children with concomitant giardiasis, we have found higher concentrations of IL-4 (9.2 ± 0.9 pg/ml) than in patients without invasion (6.7 ± 0.3 pg/ml). Combination of giardia and H.pylori affected the level of IL-4. Maximum values of IL-4 were observed in giardia monoinvasion and were significantly higher than those in H.pylori monoinfection, and when parasite invasion was combined with H.pylori, IL-4 content was decreased, while the level of TNF-α did not differ. Higher concentration of TNF-α was observed in children with increased levels of acidity, it also increased with duration of disease.